Techniques Of Teaching Speaking At The Sixth Grade Students Of SDN Cempaka Baru 05 Pagi Jakarta Pusat In 2012/2013 Academic Year - Hudani, Niki; , Aryati Prasetyarini, S. Pd, M. Pd; , Dr. Anam Sutopo, S. Pd, M. Hum (2013)
This research aims at describing teaching techniques ofspeaking to the sixth year studentsof SDN Cempaka Baru 05 Pagi Jakarta Pusat, in 2012/2013 academic year. The objectives of this research paper are to describe:1) the techniques used by the teacher in teaching speaking English, 2) the problem faced by the teacher and students in teaching learning speaking, 3) the ways of problem solving used by the teacher to overcome the problem faced by the students in learning speaking at SDN Cempaka Baru 05 Pagi. The type of this research is descriptive qualitative. The data of this research are collected by observing the English class and interviewing the English teacher. The data of this research are the sixthyear student's activities in speaking in SDN Cempaka Baru 05 Pagi in 2012/2013 academic year, field note and data from interviewing English teacher. The subject of this research is English teacher and the sixth grade students of SDN Cempaka Baru 05 Pagi, Jakarta Pusat. The object of this research is techniques in teaching speaking to the sixth year students in SDN Cempaka Baru 05 Pagi. The methods of collecting the data of the research are observation, interview, and documents. Based on the result of the analysis, the teacher uses discussion, problem solving, game, and song, as the techniques in teaching speaking. The teacher's problemsare a) the different competences of the students; b) classroom management, c) time allotment and then the problem faced by the students are a) limited vocabulary, b) student's pronunciation, c) student's self-confidence. To solve the problem a) repeat and drill vocabulary, b) the teacher give new vocabularies in every meeting, c) the teacher use game to minimize the students'anxiety.